ANALISIS INTERKONEKSI HIDRAULIKA MATA AIR DENGAN SUMUR BOR DENGAN MENGACU MERAPI METEORIC WATER LINE (MMWL) - Agus Budhie Wijatna (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2012)
The springs of Umbul Lanang (MA-1) and Umbul Wadon (MA-2) are clean water resources for the community of Yogyakarta Special Region. Operating of 5 new boreholes (SB 1-5) which is located at the same location on the southern slopes of Mount Merapi feared would reduce both of springs discharge. The objectives of this research was to determine a Merapi Meteoric Water Line (MMWL) which would be used as a reference to analyze how the hydraulic interconnection between SB and MA. This study was completed as part of a larger research of the dynamics groundwater studies using natural isotopes on the southern slope of Mount Merapi. The results showed that the isotopic composition of groundwater in the SB-1, SB-2, SB-3, SB-4 similar to the MA-1 and MA-2, and the origin of groundwater are come from the recharge zone which located at the elevation 1136 to 1260 m.asl. While the isotopic composition of SB-5 different with MA-1 and MA-2. It can be concluded that the operation of SB-1, SB-2, SB-3, SB-4 will decrease the discharge of MA-1 and MA-2, while SB-5 has no effect.